School Organizational Climate and Teachers' Productivity in Lagos State Secondary Schools - Adetoro, J. A.; Amadi, M. N. (International Journal of Educational Management, 2022)
This study investigated the relationship between school organizational climate and teachers' productivity in Lagos State secondary schools. Specifically, the study set out to examine how organizational climate influences teachers' productivity in Lagos State secondary schools. The study focused on teachers' opinion about open and close organizational climate towards their level of productivity. Two hypotheses were formulated to guide the conduct of the study. The study adopted the descriptive survey as its design while the population was made up of secondary school teachers from all the secondary schools in the four local government areas used for the study. The sample size comprised of 1,600 teachers randomly selected from the areas used for the study. Questionnaire was the only instrument used in collecting data for the study. The major findings of the study are that teachers' were motivated and encouraged to do well if the leadership is open and transparent with teachers' in secondary schools in Lagos State of Nigeria. Also, it was discovered that the inability of the teachers to give their best in terms of performance can traced to the problem associated with no consideration and poor support for teachers' on their jobs. The study recommended that to guarantee teachers' high level of productivity, management of secondary schools in Lagos State must ensure that positive consideration and support are given to teachers on their jobs all times. It is also recommended that principals and school leadership should exhibit open door policy and be transparent in their day-to-day management of secondary schools in the state.